What’s in a shape: An algorithm for finding shapes in shapes - Reis, J. (2023)
This paper describes a simple two stage algorithm for finding emergent sub-shapes in shapes, in the context of shape grammar systems. Matching the shape in the left side of a rule of a shape grammar with parts of a shape in a design in process to decide if the rule is applicable, is its main purpose. Shape grammars have been used to represent the knowledge behind the creative work of architects, designers and artists and allow the implementation of computational mechanisms to analyze and synthesize designs of visual languages, with obvious applications to design, including for marketing. Their computational mechanisms can include the detection of emergent sub-shapes. The algorithm we propose performs this task and is a core component of a system, described in our past work, that allows users to build their own shape grammars and use them.